On the Development of Long-Range Water Quality Monitoring System for Outdoor Aquaculture Objects - Pikulins, Dmitrijs; Gotlaufs, Roberts; Solovjova, Tatjana; Aboltins, Arturs; Grizāns, Juris; Migla, Sandis (Electrical, Control and Communication Engineering, 2022)
The paper is dedicated to the development of hardware and software components for the autonomous water quality monitoring system (WQMS) for fishing farms. The system can measure main water quality parameters, storing and processing data on the remote server. The LoRaWAN technological solutions and infrastructure are utilized, providing the optimal tradeoff between data transmission range and adaptive power consumption. The main implementation and exploitation issues are described, and the proposed solutions are provided.